Late Quaternary Stratigraphy and Geochronology of the Spring Creek Drainage along the Southern High Plains Eastern Escarpment, Northwest Texas - Eileen Johnson; Stance Hurst; John A. Moretti (Quaternary, 2021)
The eastern escarpment breaks of the Southern High Plains of Texas are both a geomorphic and ecotonal transition zone from the high plains surface to the Rolling Plains below. The geoarchaeological record on the Southern High Plains surface is well documented, but few studies have investigated the sediments, soils, and geochronology of the eastern escarpment. The current investigation has targeted the discontinuous remnants of Late Quaternary deposits within Spring Creek, a tributary within the upper Brazos River basin. A total of 19 profiles, core, and isolated exposure locations placed along a transect from Macy Fork through upper Spring Creek and 40 radiocarbon ages provide a composite sequence and geochronology that also documents the Late Pleistocene to Late Holocene paleoenvironments of this drainage. The resulting record illustrates a series of major changes in sediments and local habitats over the past ~11,550 radiocarbon years (13,469–13,390 calendar years), characterized primarily by reductions in available water and increasing aridity that peaked during the middle Holocene. This sequence provides significant context to an expanding record of Late Pleistocene to middle Holocene biota and cultures. Subsequent downcutting of the drainage post-6000 14C yr B.P. (6988–6744 calendar years) removed large sections of the depositional sequence. Local topography within Spring Creek drainage greatly impacted the preservation of these deposits. The remaining record provides some different insights than those available from the Southern High Plains record.